Penghimpunan Dana Zakat Infak Dan Sedekah di Badan Amil Zakat Nasional - Putra, Trisno Wardi (LAA MAISYIR : Jurnal Ekonomi Islam, 2019)
This study aims to determine the growth of the collection of zakat funds, donations / alms in the National Amil Zakat Agency. The research method used is a qualitative method with comprehensive data analysis. As a result, growth in the collection of zakat funds, infaq / alms has fluctuated where the percentage of growth has increased and decreased. As for the growth of Islamic philanthropy during 2017-2018, most of the infaq / alms then zakat instruments.